USING ARTIFICIAL INTELLIGENCE (AI)TECHNOLOGY IN THE HEALTH SECTOR HASSEVERAL GOALS - Muhammad BaballeAhmad; Shehu Hassan Ayagi; Umar Farouk Musa (IPHO-Journal of Advance Research in Science And Engineering, 2024)
In a broad sense, artificial intelligence (AI) refers to any computer or system behavior that resembles human behavior.A subfield of artificial intelligence called "machine learning" enables computers to learn from data without explicit human programming.One of the most significant contemporary trends in global healthcare is the use of artificial intelligence(AI) technologies in medicine.Technologies based on artificial intelligence are profoundly transforming the world’s healthcare system, enabling a dramatic reconstruction of the medical diagnostics system while simultaneously lowering healthcare expenditures. Identifying the class of diseases to which a disease belongs is crucial before treating it. It is feasible to categorize the type of disease based on the feature space of the condition. Algorithms for machine learning can address this issue.